2008
DOI: 10.1007/s11947-007-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Thermosonication and Pulsed Electric Fields on Staphylococcus aureus Inactivation and Selected Quality Parameters in Orange Juice

Abstract: The effect of thermosonication (TS) and pulsed electric fields (PEF) on inactivation of Staphylococcus aureus (SST 2.4) and selected quality aspects in orange juice was investigated. Conventional pasteurization (HTST, 94°C for 26 s) was used as a control. TS (10 min at 55°C) applied in combination with PEF (40 kV/cm for 150 μs) resulted in a comparable inactivation of S. aureus to that achieved by conventional HTST. TS/PEF did not affect the pH, conductivity, or°Brix and had a milder impact on the juice color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 40 publications
2
43
1
1
Order By: Relevance
“…In response to these limitations, other methods of achieving appropriate reductions in pathogenic populations are under examination as possible alternative treatments (Koutchma et al 2004;Norton and Sun 2008;Walkling-Ribeiro et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In response to these limitations, other methods of achieving appropriate reductions in pathogenic populations are under examination as possible alternative treatments (Koutchma et al 2004;Norton and Sun 2008;Walkling-Ribeiro et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The sonicated and the thermal treated samples showed ascorbic acid values in the same range. Thermosonication treatment also retained high levels of ascorbic acid in a study with orange juice reported by Walkling-Ribeiro et al (2007). Murcia et al (2000), in a study in which broccoli florets were industrially processed, showed that blanching for 60 s at 92-96°C maintained about 50% of vitamin C content and reduced 99% of peroxidase activity.…”
mentioning
confidence: 81%
“…The effect of thermo-sonication (TS) and PEF on inactivation of S. aureus and selected quality aspects in orange juice was investigated (Walkling-Ribeiro et al 2009). TS (10 min at 55°C) applied in combination with PEF (40 kV/cm for 150 μs) resulted in a comparable inactivation of S. aureus to that achieved by conventional HTST.…”
Section: Orange Juicementioning
confidence: 99%